2017
DOI: 10.1117/1.nph.4.4.041408
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of data-driven optical neuromonitoring approach during general anesthesia with sevoflurane

Abstract: Anesthesia monitoring currently needs a reliable method to evaluate the effects of the anesthetics on its primary target, the brain. This study focuses on investigating the clinical usability of a functional near-infrared spectroscopy (fNIRS)-derived machine learning classifier to perform automated and real-time classification of maintenance and emergence states during sevoflurane anesthesia. For 19 surgical procedures, we examine the entire continuum of the maintenance-transition-emergence phases and evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…In contrast to conventional approach that uses ΔHbO for FC analysis, we also used ΔHb due to previous evidence that suggests both hemoglobin concentrations should be analyzed for sparse networks (Montero-Hernandez et al, 2018b). In addition to this, there are several fNIRS based ML studies that focuses on classification of several psychiatric disorders also uses ΔHb (Cheng et al, 2019; Crippa et al, 2017; Hernandez-Meza et al, 2018; Hernandez-Meza et al, 2017; J. Li et al, 2016; Rosas-Romero et al, 2019; Sirpal et al, 2019; Sutoko et al, 2019) and for some cases ΔHb based features might also show higher accuracy results compared to ΔHbO based ones (Crippa et al, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…In contrast to conventional approach that uses ΔHbO for FC analysis, we also used ΔHb due to previous evidence that suggests both hemoglobin concentrations should be analyzed for sparse networks (Montero-Hernandez et al, 2018b). In addition to this, there are several fNIRS based ML studies that focuses on classification of several psychiatric disorders also uses ΔHb (Cheng et al, 2019; Crippa et al, 2017; Hernandez-Meza et al, 2018; Hernandez-Meza et al, 2017; J. Li et al, 2016; Rosas-Romero et al, 2019; Sirpal et al, 2019; Sutoko et al, 2019) and for some cases ΔHb based features might also show higher accuracy results compared to ΔHbO based ones (Crippa et al, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…Taking this concept further, Hernandez-Meza et al developed a functional NIRS based machine learning classifier to classify, in real-time, maintenance and emergence states in 19 patients undergoing various surgical procedures with sevoflurane anesthetic. They found that their NIRS based system was able tot detect emergence prior to bispectral index (BIS; Hernandez-Meza et al, 2017). These studies point to a possible role for NIRS in the tailored titration of sedation in the acute setting.…”
Section: Near-infrared Spectroscopy In Intraoperative Monitoring Of Traumatic Brain Injury Patientsmentioning
confidence: 96%
“…Two studies were reported to classify the anesthesia phases. In the first study, fNIRS data collected under different anesthesia conditions from 19 patients under surgery was used for analysis (Hernandez-Meza et al, 2017). In this study, anesthesia conditions were identified as maintenance (MC) and emergence (EC).…”
Section: Anesthesia Monitoringmentioning
confidence: 99%
“…SVM is a robust supervised learning algorithm that aims to discriminate the input data by creating a hyperplane with maximum margin according to their previously defined labels as we addressed in the section 5.1 (Vapnik, 1995). It was the most preferred classifier among fNIRS studies (Abtahi et al, 2020; Al-Shargie et al, 2017b; Cheng et al, 2019; Crippa et al, 2017; Dadgostar et al, 2018; Einalou et al, 2016; Eken et al, 2019; Fernandez Rojas et al, 2017, 2019; Gokcay et al, 2019; Gu et al, 2018; Guevara et al, 2020; Hernandez-Meza et al, 2018; Hernandez-Meza et al, 2017; Hosseini et al, 2018; Ichikawa et al, 2014; Karamzadeh et al, 2016; J. Li et al, 2016; Z.…”
Section: Machine Learning In Fnirsmentioning
confidence: 99%
See 1 more Smart Citation